The Position and Responsibilities of the Beneficiaries of the Limited Liability Company in ViewRegulation of the President of the Republic of Indonesia Number 13 of 2018 - Sarah Fauziah (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
Issuance of Regulation of the President of the Republic of Indonesia number 13 in 2018 regarding how to apply the principle of identifying the beneficiary. Cases of criminal acts of money laundering and financing of terrorists in the State of Indonesia under the guise of or by hiding the proceeds of such criminal behavior within a company. The purpose of this researchto find out the position the beneficial owner of the Limited Liability Company in terms ofRegulation of the President of the Republic of Indonesia number 13 of 2018 and to know responsibility the beneficial owner of the Limited Liability Company in terms ofRegulation of the President of the Republic of Indonesia number 13 of 2018. The method used in this study is the Normative Juridical method, the specifications in this study are analytical descriptive, the data used are primary data and secondary data, using data collection by interviews and literature studies, qualitative data analysis, problems are analyzed by theory, law enforcement and legal certainty. The results of this study indicate that an equal position between beneficial ownership and major shareholders is based on the beneficial ownership rights described in Presidential Decree No. 13 of 2018. Thus, beneficial ownership can be subject to personal responsibility based on the principle of piercing the corporate veil contained in the Act No. 40 of 2007 concerning Limited Liability Companies, both jointly and or individually in committing money laundering crimes. However, currently there are no technical regulations that include sanctions for companies in the event of non-compliance with BO transparency.